Dietetic management of obesity and severe obesity in children and adolescents: A scoping review of guidelines. (7th September 2020) - Alman, Kim L.; Lister, Natalie B.; Garnett, Sarah P.; Gow, Megan L.; Aldwell, Katharine; Jebeile, Hiba
Summary: This scoping review describes current guidelines for the dietary management of pediatric obesity and severe obesity. Guidelines were identified via electronic searches of six databases, grey literature, and reference lists and included international clinical practice guidelines ( n = 21), position papers ( n = 5), and scientific/consensus statements ( n = 2) produced by professional bodies and/or expert panels. All recommend multicomponent lifestyle interventions including diet, physical activity, and behavior modification as first‐line treatment. Most guidelines ( n = 21) recommend weight loss as a treatment goal for children and adolescents with obesity and associated comorbidities or severe obesity; 15 recommend using dietary approaches. Fourteen of 28 guidelines refer to the management of severe obesity, 10 refer to dietary approaches, and seven recommend using intensive dietary approaches. Dietary approaches to weight loss focus on caloric restriction ( n = 14) with some guidelines recommending very low‐energy diet ( n = 4), protein‐sparing modified fast ( n = 2), and very low‐carbohydrate/ketogenic diets ( n = 2). A stronger evidence base is required for dietary management of pediatric obesity and severe obesity to improve consistency in future guidelines. Guidance on the use of dietary approaches, beyond caloric restriction, and in line with the growing evidence base on novel dietary approaches is required to facilitate personalized care and optimal patient outcomes.